Organizational Culture: A Bibliometric Review of Knowledge Clusters and Thematic Evolution - Loso Judijanto; Heri Setiyawan (Westscience Press, 2026)
This study aims to map the intellectual structure, knowledge clusters, and thematic evolution of organizational culture research through a bibliometric approach. Data were collected from the Scopus database within a defined publication period and analyzed using VOSviewer to identify co-occurrence patterns, research clusters, and temporal trends. The findings reveal that organizational culture serves as a central construct connecting multiple research domains, particularly leadership, employee well-being, job satisfaction, and organizational performance. Cluster analysis indicates that the literature is dominated by themes related to organizational behavior, psychological dimensions, and healthcare applications, highlighting the importance of culture in shaping both employee outcomes and operational effectiveness. Thematic evolution analysis further demonstrates a shift from traditional topics such as values and organizational behavior toward emerging themes including digital transformation, artificial intelligence, and sustainability. Density visualization confirms that while core themes remain highly developed, newer areas are gaining increasing scholarly attention. This study contributes to the literature by providing a comprehensive and systematic overview of the development of organizational culture research, offering insights into its current state and identifying potential directions for future studies in a rapidly changing organizational landscape